Microstructural evolution and mechanical properties of maraging steel produced by wire + arc additive manufacture process - Xu, Xiangfang; Ganguly, Supriyo; Ding, Jialuo; Guo, Shun; Williams, Stewart W.; Martina, Filomeno (Elsevier, 2017)
Wire + arc additive manufacture is developed for producing large-scale metallic components. In this paper, maraging steel parts were produced, and the microstructure and mechanical properties were investigated. The microhardness and tensile strength of the as deposited alloy reduced from the bottom to the top due to the transient thermal cycling, which resulted in partial aging and non-uniform formation of intermetallic compounds along the building direction. Solutionizing, followed by 3 h aging, significantly reduced the microstructural heterogeneity and increased the mechanical properties by 24.7% through the formation of large amounts of finely distributed precipitates. The as deposited alloy possessed superior strength to the wrought alloy in solutionized condition but inferior to the later in aged condition, which was attributed to the less pronounced aging response of the low-angle columnar grains characterized microstructure and the presence of retained and reverted austenite.
Keywords: Wire + arc additive manufacture; Maraging steel; Precipitates; Mechanical properties; Heat treatment